Study on the profile of specific speed level among U20 long jumpers in Romania - Calfa, H.; Mihailescu, L. (Journal of Physical Education and Sport, 2023)
The purpose of this study was twofold: first, to determine the physical characteristics of U20 (under 20) long jumpers to identify the level of speed parameters during the last 10 m of the run-up and the last three steps of the run-up, thus profiling the specific speed level of the research subjects; second, to ascertain whether the level of horizontal speed at takeoff influences the performance obtained in the competition, both as a group and as an individual tendency. The study involved eight female long jump athletes who were finalists of CN Outdoor U20 and were aged between 15 and 18 years (M = 16.87, S = 0.75).